Budaya Melayu dan Pengaruh Islam dalam Upacara Pernikahan di Tanjung Balai - Ahmad Gifari Alamsyah; Andhika Nugraha; Muhammad Reza; Hasan Sazali; Maulana Andinata Dalimunthe (Prodi Pendidikan Sejarah Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Sumatera, 2022)
This study aims to find out how the series of traditional wedding ceremonies of the Tanjung Balai Malay tribe and what are the Islamic values contained in it and to understand how the relationship between Islam in each wedding procession and what are the meanings contained in it. This research uses qualitative research methods, and this research can be categorized as field research. The resulting data sources are in the form of primary and secondary data, the writing method used in this study is descriptive qualitative, namely research to provide geographical conditions for certain communities. The results of the study explained that from the various processions of the traditional ceremonies of the Tanjung Balai Malay wedding reception, not all of them were based on Islamic law, but followed the hereditary customs of the Malay people that have existed since ancient times. The traditional ceremonies based on Islamic law include merisik, proposal, delivery/offering, ijab qabul, khatam kaji and parade.